Social Platforms in the Deepfake Age: Navigating Media Trust through Media Literacy - Lee, Fong Yee; Kumaresan, S Prabha; Abdulwahab Anaam, Elham; Chee Kong, Wong (JOIV : International Journal on Informatics Visualization, 2025)
The issues with social media landscape are proliferation of disinformation, misinformation, and misinformation. The widespread of deepfakes makes is harder to distinguish between authentic content and fabricated content. The mediating effect of media literacy on news credibility has been understudied in previous research; the objective of the study is to investigate how much media literacy, news skepticism and fear of missing out (FOMO) influencing users' trust in the news disseminated on social media platforms. To achieve this, a survey was conducted to assess trust in and skepticism towards social media news, FOMO levels, and media literacy associated with deepfake news content. Educational efforts and media literacy initiatives are crucial in fostering informed and discerning news consumption. Furthermore, news organizations continue to prioritize transparency and accuracy to maintain credibility on social media since the news is easily accessible in the era of an information overload. The limitation of the study was the lack of assessment on evaluating effectiveness of media literacy in combating fabricated news content on social media. It is suggested to broaden scope by studying additional factors to combat fake news such as journalistic standards, fact-checking and verification are important to build reader’s trust. Future studies should also measure the effectiveness of media literacy initiatives ensure they really make a difference. The generalizability of future study can be strengthened with the inclusion of diverse age groups especially vulnerable populations.